2022
DOI: 10.1177/17456916221121815
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Multisite Replication Projects in Social Psychology: Is It Viable to Sustain Any Confidence in Social Psychology’s Knowledge Base?

Abstract: Multisite (multilab/many-lab) replications have emerged as a popular way of verifying prior research findings, but their record in social psychology has prompted distrust of the field and a sense of crisis. We review all 36 multisite social-psychology replications (plus three articles reporting multiple ministudies). We start by assuming that both the original and the multisite replications were conducted in honest and diligent fashion, despite often yielding different conclusions. Four of the 36 (11%) were cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 108 publications
0
18
0
Order By: Relevance
“…Our purpose in this article is to elaborate on the results and conclusions from that earlier paper (Baumeister et al, in press). We refer interested readers to that article for full details.…”
Section: Results Of Review and Meta-analysismentioning
confidence: 81%
See 3 more Smart Citations
“…Our purpose in this article is to elaborate on the results and conclusions from that earlier paper (Baumeister et al, in press). We refer interested readers to that article for full details.…”
Section: Results Of Review and Meta-analysismentioning
confidence: 81%
“…An exhaustive literature search yielded 36 articles that reported a multi-site replication project in social psychology (Baumeister et al, in press). There were some additional papers filled with what we called mini-studies.…”
Section: Results Of Review and Meta-analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the validity of the laboratory work, it seems clear that many scientific fields suffer from problems of replicability, and social psychology’s may be especially problematic. Open Science Collaboration (2015) found social psychology experiments replicated at lower rates than cognitive psychology, and a recent survey of all 36 multi-site replications in social psychology found that only four produced significant findings consistent with the original (and most of those with reduced effect sizes; Baumeister et al, in press). Within that turbulent context, however, ego depletion has a strong case to be considered the best-replicated finding in social psychology (Baumeister & Tice, 2022).…”
Section: Generalizability and External Validity Of Self-regulatory De...mentioning
confidence: 99%